Area-based development of ecologically sensitive urban areas: systematic literature review to understand prevailing concepts and practices - Deeksha Chhachhiya; Ashwani Kumar; Satish Pipralia (Discover Cities, 2025)
Abstract The Global phenomenon of Urbanization continues to accelerate considerably and, it is crucial to acknowledge that this expansion is not evenly distributed worldwide. While Urbanization is considered crucial for national development, it simultaneously disrupts and degrades Ecologically Sensitive Areas, creating significant environmental and socio-ecological challenges. Urban areas located within or near Ecologically Sensitive areas are vital for play a crucial role in preserving ecological equilibrium and safeguarding both urban environmental and ecological safety; however, they often endure substantial developmental pressures that threaten the sustainability of both human and natural systems. In this context, security of urban environment becomes increasingly significant which refers to the protection of urban populations and infrastructure from environmental risks and ecological degradation while ensuring the continued provision of essential ecosystem services that sustain life and development. The urban areas which are located in hilly ecologically vulnerable areas face even more critical challenges due to complex topography, adverse climatic conditions, intricate geological formations and fragile ecosystems. Balancing urban growth with environmental conservation in such areas represents not only a major localized concern but also a globally relevant challenge. Urban environmental security in these areas acquires an added layer of complexity, as the fragility of the surrounding ecosystems directly influences the vulnerability of urban systems. Ensuring urban environmental security in ecologically sensitive settings therefore requires integrated, precautionary urban planning and governance strategies which must harmonize development needs with ecological conservation imperatives, strengthening the capacity of cities to withstand and adapt to environmental stresses. This paper aims to present a thorough overview of the literature concerning the most commonly utilized concepts and approaches for development in ecologically sensitive urban areas, with particular emphasis on hilly urban areas. By systematically analyzing 81 selected articles from 1697 publications, this study critically compares existing concepts, programmes or approaches for urban development adopted not only to Indian hill towns but also to fragile urban ecosystems globally, while highlighting their similarities and differences, and pinpointing any gaps in order to assess their effectiveness and suitability in addressing the multifaceted issues of area-based development for hill towns in ecologically sensitive areas. Furthermore, by synthesizing the insights across diverse contexts, the review offers valuable alternatives for policymakers, planners and scholar engaged in the sustainable development of ESAs worldwide. It emphasizes the urgent need for area-based, resilience oriented approach to urban planning while ensuring Socio-Ecological development of the concerned areas. Thus, it’s an attempt to identify the gaps in the subject area while suggesting a better alternative to plan and design an urban area while maintaining the ecological balance and ensures sustainability of the concerned setting.